Safety Evaluation of Parastar® Plus in Dogs and Assessment of Transferable Residue of Fipronil and Cyphenothrin from Dogs to Humans - Case, Katharine M.; Vega, Natalia M.; Gupta, Ramesh C.; Lasher, Michelle A.; Canerdy, Terry D. (Frontiers in Veterinary Science, 2016)
Currently, the world’s dog population is estimated at 900 million (>80 million in the US, 15.9 million in Russia, 8.5 million in the UK, 7.3 million in France, 7 million in Italy, and 6.9 million in Germany). Dogs are easily infested with fleas, ticks, and other ectoparasites serving as vectors for transmitting bacterial, viral, and parasitic diseases. Therefore, the use of ectoparasiticides is inevitable and important. The present investigation was undertaken with two specific objectives: one, to evaluate the safety of fipronil and cyphenothrin in dogs after topical application of Parastar ® Plus, and two, to determine the transferable residue of these insecticides from dogs to humans. Six healthy, adult dogs (medium length hair, weighing between 20.5-27.3 kg) received topical application of Parastar ® Plus (2.68 mL; fipronil, 9.8% and cyphenothrin, 5.2%) on the back between the shoulder blades. At pre-determined intervals, dogs were given a full physical exam, and residues of fipronil and cyphenothrin were determined in dog blood and cotton glove extracts using GC/MS. Fipronil and cyphenothrin peaks eluted at 7.453 and 9.913 min, correspondingly, and the compounds were confirmed based on characteristic ions. At no time was fipronil or cyphenothrin residue detected in blood samples. In glove extracts, residues of fipronil and cyphenothrin were maximally present at 24 hr post-treatment (43.84 ± 5.69 and 59.26 ± 8.97 ppm, respectively). By 48 hr, the residue levels sharply declined (16.89 ± 2.82 and 17.98 ± 2.07 ppm, respectively). The insecticides’ residues were detected in insignificant amounts after one week (5.69 ± 2.16 and 10.00 ± 1.51 ppm, respectively), and only in trace amounts after two weeks. At no time did any dog show side effects, except itching at the site of Parastar ® Plus application. The findings suggest that Parastar ® Plus was safe for dogs and transferable residues of fipronil and cyphenothrin were minimal, posing very little or no health concern to pet-owners or veterinary personnel. Of course, veterinary personnel, who handle many dogs daily, may require proper protection to avoid cumulative exposure. Keywords: Parastar ® Plus; fipronil; cyphenothrin; pyrethroids; ectoparasiticide safety; dogs.